PENGARUH JARAK TANAM TERHADAP PERTUMBUHAN DAN PRODUKSI TIGA AKSESI JAGUNG PULUT LOKAL MAROS - Setyowati, Ninik; Utami, Ning Wikan (JURNAL AGROTROPIKA, 2020)
The research on the effect of planting space treatment on the growth and yield of three accessions of local maize from Maros, Sulawesi Selatan was carried out at the Experimental Garden of Research Center for Biology LIPI, Cibinong on May – August 2012. The research study was arranged by Factorial in Randomized Completely Block Design with 2 factors and 4 replications, each replication with 10 plant samples. The first factor was accession of pulut local maize (sticky rice maize) with 3 levels factor i.e. Snack Pulut, Rice Pulut and Hybrid Pulut. The second factor was planting space treatment with 3 levels factor i.e. planting space of 100x20 cm, 80x20 cm and 60x20. The treatment of accession was significantly on the vegetative growth of Pulut corn. Accession Rice Pulut growth was the fastest (116.3 cm plant height, 11.5 number of leaves), compared to Snack Pulut (91.2 cm plant height, 7.6 leaves), and accession Hybrid Pulut (111.9 cm height, 8.2 leaves). All of accession showed flowering (70-90 %) at 7 weeks after planting. Accession of Snack Pulut showed fruiting (90%) faster than Hybrid Pulut (80%), and Rice Pulut (20%). Accession Rice Pulut showed the highest production compared to Snack Pulut and Hybrid Pulut, but has the longest harvest (12 weeks). Accession of Snack Pulut was the fastest harvesting (9 weeks), followed by Hybrid Pulut (10 weeks). The planting space treatments were not significantly different on the growth and production of sticky rice maize, so tight spacing (60x20 cm) may be used to increase yield. Key words: Planting space, growth, yield, accessions, local maize, Maros